The structure of compact groups a primer for the student, a handbook for the expert - Hofmann, Karl Heinrich (De Gruyter studies in mathematics ;, 2020)
This book is designed both as a textbook for high-level graduate courses and as a reference for researchers who need to apply the structure and representation theory of compact groups. A gentle introduction to compact groups and their representation theory is followed by self-contained courses on linear and compact Lie groups, and on locally compact abelian groups. This fourth edition was updated with the latest developments in the field.